Q-Fever, an undermined zoonotic threat - Shrestha, Swochhal Prakash; Kaphle, Krishna; Panth, Yuvraj; Shrestha, Swoyam Prakash (Journal of Agriculture and Natural Resources, 2020)
With upto 75% of all human disease being zoonotic in origin, proper study of the diseases is necessary to prevent any outbreak or human loss. More studies are required for developing countries like Nepal where there are no appropriate provisions for situations after breakouts. One such little known sporadic zoonosis is Q-fever. Q-fever (Coxiellosis) is caused by Gram-negative bacterium Coxiella burnetii that infect cattle and other ruminants with serious concerns for developing reproductive disorders and flu-like symptoms in human. There have been reports of undifferentiated febrile illness of Rickettsial cause in human and seroprevalence of Coxiella antibodies in goats of Chitwan and dairy cattle of Rupandehi for the first time. Low infectious dose and high resistivity to environment makes the disease more potent. Q-fever continues to be unexplored in Nepal despite its identification in neighboring countries like India. Thus, this paper after reviewing related articles from various journals, proceedings and magazines from online sources like Google Scholar, Mendeley, NCBI and PubMed is aimed to evaluate current status of disease, its epidemiology, zoonotic potential and preventive measures that can be adopted to minimize the threat of the disease as much as possible.